Plasmid-associated clonal expansion drives department-preference transmission of carbapenem-resistant Klebsiella pneumoniae in Xi’an, China: a genomic epidemiology study - Luo, Kai; Liu, Shuyan; Feng, Jie; Li, Ruichao; Zhang, Sirui; Yu, Rong; Li, Fang; Li, Yali; Wu, Ke; Wang, Juan; Xie, Ting; Lei, Jin’e; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundThe drivers of expanding carbapenem-resistant Klebsiella pneumoniae (CRKP) infections in Northwest China remain poorly understood. This study aimed to investigate the clinical and molecular epidemiology of CRKP infections in Xi’an, China.MethodsWe conducted a comprehensive analysis in a tertiary teaching hospital (September 2017–December 2019) by clinical data evaluation, antimicrobial susceptibility testing, and genome sequencing to characterize sequence types (STs), resistance and virulence genes, and plasmid profiles.ResultsCRKP isolation rate increased from 3.6% to 17.2% during 2017-2019. Of 140 cases, 31.43% occurred in the Department of Hepatobiliary Surgery and 31 (22.14%) in the ICU, with a predominance among elderly male patients. Surgery and interventional therapy were performed in 50.7% and 25.7% of cases, respectively. Among 23 STs identified, ST11 (72.1%) was the most prevalent and exhibited high rate of multidrug resistance, commonly associated with narrow-spectrum β-lactamases-coding genes (highest in 110/140), blaKPC-2 (106/140), rmtB (85/140), oqxAB (110/140) and fosA (110/140). Virulence factors involved in secretion systems, iron uptake, and adhesion were identified. ST11 strains frequently carried IncFII, IncR and ColRNAI plasmids, while IncFIB-type was more relevant to ST147. Notably, strains harboring plasmid combinations IncFIIpHN7A8:IncR:ColRNAI and IncFIIpHN7A8:IncR:ColRNAI:IncFIB(K)-1-kpn3 were responsible for CRKP infections in the Department of Hepatobiliary Surgery and ICU, and exhibited higher resistance levels to carbapenems.ConclusionsDepartment-specific plasmid combinations considerably increased CRKP infection and multidrug resistance rates. Surgical and interventional therapies were vital factors contributing to CRKP infections, especially in elderly male patients.